Green zone nation : the securitisation and militarisation of the 2010 FIFA World Cup, South Africa - McMichael, Christopher Bryden (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2013)
This thesis explores the relationship between the safety and security measures for the 2010 FIFA World Cup and the militarisation of urban space and policing in post-apartheid South Africa. In particular, it focuses upon how the South African state and FIFA, the owners of the World Cup franchise, worked to present the World Cup as an event which required exceptional levels of security "“ resulting in a historically unprecedented joint police and military operation across host cities. However, in contrast with previous research on these security measures, this thesis aims to interrogate the political and commercial forces which constructed security and positions them against a backdrop of intensified state violence and social exclusion in South Africa. Concurrently, the South African case was indicative of an international militarisation of major events, with policing operations comparable to national states of emergency. This is representative of the 'new military urbanism' in which everyday urban life is rendered as a site of ubiquitous risk, leading to the increased diffusion of military tactics and doctrines in policing and policy. While the interpenetration between urbanism and militarism has often been studied against the context of the 'war on terror', in the case of South Africa this has primarily been accelerated by a pervasive social fear of violent crime, which has resulted in the securitisation of cities, the remilitarisation of policing and the intensification of a historical legacy of socio-spatial inequalities. The South African government aimed to use the World Cup to 'rebrand' the country's violent international image, while promising that security measures would leave a legacy of safer cities for ordinary South Africans. The concept of legacies was also responsive to the commercial imperatives of FIFA and a range of other security actors, including foreign governments and the private security industry. However these policing measures were primarily cosmetic and designed to allay the fears of foreign tourists and the national middle class. In practice security measures pivoted around the enforcement of social control and urban marginalisation while serving as a training ground for an increasingly repressive state security apparatus. Security was as much a matter of fortifying islands of privilege and aiding a project of financial extraction as protecting the public from harm.,Microsoftï¿½ Office Word 2007,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: World Cup (Soccer) (2010 : -- South Africa) -- Safety measures -- Research; Fédération internationale de football association; Militarism -- Research -- South Africa; Sports -- Political aspects -- Research -- South Africa; Police -- South Africa; South Africa -- Armed Forces; Crime -- South Africa; Violent crimes -- South Africa; Violent crimes -- South Africa